Effectivity of mulberry leaf extract on stimulating ekdisteroid hemolimph content and molting of mud crab (Scylla olivacea) (Torani Journal of Fisheries and Marine Science, 2019)
This study aims to study the performance of phytoecdisteroids from mulberry leaves in molting stimulating of mangrove crabs. The research was carried out at the Research and Development Center for Aquaculture at the Faculty of Marine Sciences and Fisheries at Hasanuddin University, located in Bojo Village, Mallusetasi District, Barru Regency, South Sulawesi Province. Mangrove crabs (Scylla olivacea) weighing 45-55 g and carapace widths 60-65 mm were used as test animals. There were five doses of mulberry leaf extract applied through feed, namely: A) 1.1 mg / g feed, B) 1.9 mg / g feed, C) 2.7 mg / g feed, D) 3.5 mg / g feed. Crabs were kept individually in plastic boxes that are floated above the surface of the pond. During rearing, crabs are fed 3% dry fish per day which has been enriched with mulberry leaf extract. The parameters observed were ecdysteroid compounds contained in mulberry leaf extract, ecdysteroid content in hemolymph before and after application of mulberry leaf extract, and molting percentage. Identification of the ekdisteroid compounds contained in mulberry leaf extract was carried out using Thin Layer Chromatography (TLC) and Measurement of the content of ecdysteroids in crab hemolymh was carried out using Ultra Fast Liquid Chromatography (UFLC).  The results showed that the 3.5 mg dose of mulberry leaf extract / g feed gave the highest increase in ecdysteroid hemolymph, which was approximately 1760 ekdisteroid per mL hemolimph, while the dose of 1.1 mg / g feed only provided an increase of 100 ng ekdisteroid per mL hemolymph. The higher the dose of mulberry leaf extract in the feed, the higher the increase in the concentration of hemolymph ecdysteroids, but the high concentration of ecdystoid in the hemolymph does not guarantee molting.  The optimal dose of mulberry leaf extract in the feed stimulating molting was 2.4 mg / g of feed.Keywords: mulberry, phytoecdysteroid, molting, crab, aquaculture